Private and Public Supply of Liquidity - Holmström, Bengt; Tirole, Jean (Journal of Political Economy, 1998)
This paper addresses a basic, yet unresolved, question: Do claims on private assets provide sufficient liquidity for an efficient functioning of the productive sector? Or does the state have a role in creating liquidity and regulating it either through adjustments in the stock of government securities or by other means? In our model, firms can meet future liquidity needs in three ways: by issuing new claims, by obtaining a credit line from a financial intermediary, and by holding claims on other firms. When there is no aggregateuncertainty, we show that these instruments are sufficient for implementing the socially optimal (second‐best) contract between investors and firms. However, the implementation may require an intermediary to coordinate the use of scarce liquidity, in which case contracts with the intermediary impose both a maximum leverage ratio and a liquidity constraint on firms. When there is only aggregate uncertainty, the private sector cannot satisfy its own liquidity needs. The government can improve welfare by issuing bonds that commit future consumer income. Government bonds command a liquidity premium over private claims. The government should manage debt so that liquidity is loosened (the value of bonds is high) when the aggregate liquidity shock is high and is tightened when the liquidity shock is low. The paper thus suggests a rationale both for government‐supplied liquidity and for its active management.